Seeing spots : a functional analysis of presidential television advertisements, 1952-1996 - Benoit, William L. (Praeger series in political communication., 1999)
Benoit provides a comprehensive analysis of presidential spots from the inception of this important message form in 1952 through the most recent national campaign in 1996. He includes both primary and general spots as well as those from third party candidates.